2021
DOI: 10.1021/acsaelm.0c01003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Structural Studies and the Cathodoluminescence of Individual Complex Niobate Particles

Abstract: Lanthanide-doped semiconductors and the mechanism of energy transfer from host to lanthanide ions have always been a topic of great interest. In this study, we underline the effect of the lanthanide ions’ surroundings on the width of the emission lines. We show that different crystal structures and lattice defects within the crystal lead to different atomic coordinates of the ion. In this work, complex niobates synthesized in a solid-state route were investigated. Because of the micron size of the particles, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 32 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…Because higher emission lines are observed for the twinned areas, we believe that these crystal defects are perturbing f–f transitions, resulting in increased intensity. Based on these results and our recent findings published in ref , the high amount of Pr in addition to the presence of defects in PrNbO 4 makes these particles excellent luminescent materials. Moreover, we showed with our multitechnique approach that higher density of the twins leads to the strongest luminescence brightness, and therefore they are better candidates to be used in optical applications.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Because higher emission lines are observed for the twinned areas, we believe that these crystal defects are perturbing f–f transitions, resulting in increased intensity. Based on these results and our recent findings published in ref , the high amount of Pr in addition to the presence of defects in PrNbO 4 makes these particles excellent luminescent materials. Moreover, we showed with our multitechnique approach that higher density of the twins leads to the strongest luminescence brightness, and therefore they are better candidates to be used in optical applications.…”
Section: Resultssupporting
confidence: 83%
“…This reaction was done to obtain particles with the nominal formula Pr x K 1– x Ca 2– x Nb 3 O 10 . X-ray diffraction reported in ref showed the formation of two phases, namely, Pr 3+ :Ca 2 Nb 2 O 7 and PrNbO 4 . PrNbO 4 particles were produced due to the excess of Pr.…”
Section: Experimental Proceduresmentioning
confidence: 94%
See 2 more Smart Citations
“…The optical properties of individual nanosheets with different thicknesses are correlated to their crystal structure and chemical composition obtained via transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). We found that due to the lower Pr content observed in the nanosheets compared to bulk particles 10 , 11 , different luminescence properties are observed.…”
Section: Introductionmentioning
confidence: 84%